2019
DOI: 10.1097/meg.0000000000001417
|View full text |Cite
|
Sign up to set email alerts
|

Occult hepatitis B and HIV infection

Abstract: Introduction Occult hepatitis B virus (HBV) infection, so-called occult B infection (OBI), is defined by the recognition of HBV-DNA in the absence of serum hepatitis B surface antigen (HBsAg). The HBV-DNA genome in OBI is fully replication competent and produced in the liver, characteristically with low-level HBV-DNA fluctuations in the bloodstream. The OBI status remains between chronic (HBsAg +) and resolved (anti-HBs +) phases in the natural history of HBV infection. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 45 publications
0
16
0
Order By: Relevance
“…Mutant viruses may escape serological diagnosis using specific anti-HBs antibodies, causing occult forms of chronic hepatitis B. 22 Given that HBV sequencing was not successful in any of our specimens with OBI, most likely due to low HBV-DNA amounts, as shown by others, 19,20 we could not investigate further HBsAg-negative infections, but it cannot be disregarded that some of them contained drug-resistance mutations. Our numbers stress that OBI could be a significant source of virus contamination in blood donations in many resource-limited clinical settings, since HBV-DNA is not routinely tested by sensitive and reliable procedures.…”
Section: Discussionmentioning
confidence: 93%
“…Mutant viruses may escape serological diagnosis using specific anti-HBs antibodies, causing occult forms of chronic hepatitis B. 22 Given that HBV sequencing was not successful in any of our specimens with OBI, most likely due to low HBV-DNA amounts, as shown by others, 19,20 we could not investigate further HBsAg-negative infections, but it cannot be disregarded that some of them contained drug-resistance mutations. Our numbers stress that OBI could be a significant source of virus contamination in blood donations in many resource-limited clinical settings, since HBV-DNA is not routinely tested by sensitive and reliable procedures.…”
Section: Discussionmentioning
confidence: 93%
“…A recent South African prospective study investigating the impact of 3TC-containing ART regimens on the trend of HBV viremia during 24 months of follow-up demonstrated that 25% of patients with proven OBI had detectable HBV DNA at 24 months after the introduction of 3TC [12]. In addition, the possibility of HBVimmune escape mutant emergence is a well-known phenomenon in patients treated with 3TC [2].…”
Section: Discussionmentioning
confidence: 99%
“…Patients with OBI may or may not have serological signs of a previous HBV infection; however, the presence of antibodies against an HBV c antigen (HBcAb) is usually considered a surrogate marker of an OBI condition [1]. Immunosuppression is often related to a deficiency in the HBV immune response resulting in the development of chronic or occult HBV infection, and cancers, immunosuppressive treatments, and human immunodeficiency virus (HIV) infection are known to predispose patients to OBI [2]. OBI is quite common in patients living with HIV (PLWH), particularly in countries with a high HBV prevalence [3,4], and low CD4+ counts or AIDS-related diseases are more common in PLWH with OBI treated or not with antiretroviral therapy (ART) [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…Though most studies [ 32 , 33 , 34 , 35 , 36 , 37 , 38 ] showed high clinical sensitivity of 89–100% in the general population, the reported sensitivity varied widely in HIV-infected populations (56–100%) [ 39 , 40 , 41 , 42 , 43 , 44 ]. The cause of the reported lower sensitivity in HIV-coinfected populations [ 39 , 40 , 43 , 44 ] is unclear, but potential reasons may include the cross reaction of HIV-reverse transcriptase inhibitors and hepatitis B virus, a higher rate of occult hepatitis B infection in early HIV cohorts, a higher reported rate of HBsAg loss in both untreated and treated HIV-infected populations and the use of tenofovir-based HIV regimens that effectively suppress hepatitis B virus DNA levels and a large decline in HBsAg titres [ 31 , 45 , 46 ]. SD Bioline HBsAg [ 38 , 47 , 48 , 49 ] and VIKIA HBsAg POC test [ 32 , 33 , 38 , 50 , 51 ] have also been shown to have good sensitivity (above 90%) and excellent specificity (above 99%) in general populations; however, lower sensitivity was also reported in HIV-infected populations [ 40 ].…”
Section: Poc Tests For Hepatitis B and Their Clinical Performancementioning
confidence: 99%